Indicators Of Mineral Density Of Bone Tissue And Levels Of Calciotropic Hormones In Children And Adolescents With Thyroetoxicosis - Shakhlo Muratova (International Journal of Advanced Science and Technology, 2020)
Introduction. In childhood and adolescence, a genetically determined bone mass accumulates, which ensures the strength of the skeleton throughout life. But with thyrotoxicosis, a separation of the processes of bone resorption and synthesis and the formation of sites of osteoporosis and osteosclerosis occur, leading to the loss of 10% of bone mass in 1 cycle of remodeling. Because of the lack of information about this phenomenon, our work aimed to study the state of bone mineral density and levels of calciotropic hormones in children and adolescents with thyrotoxicosis.